Estudo da utilização de vídeos 360º na experiência turística - Mariana de Oliveira Magalhães (2017)
Tourism has been considerably changing in parallel with the Information and Communication Technologies (TIC) evolution. These changes are fundamental for the way information is available and accessed, as well for the way touristic products/services can be purchased and experienced. The introduction of new technological tools in tourism promotion, highlighting 360º video and Virtual Reality (VR), are an increasingly current reality. Its alliance allows the user to be in the center of the action, visualizing the whole scenario in a more immersive way, through VR equipment. This investigation focus on their combination. In this regard, three situations are reviewed: two 360º video visualization about two different touristic places, one with VR equipment and the another without it; and then, a physical visit to those places. By comparing these three situations, it was intended to: determine the impact of "age" and "education level" (independent variables) for participants' sense of presence (SP) on Virtual Experiences (VE); on the other hand, it was sought to find out if these variables affect the users' perception of the virtual environment, concerning to "expectancy/reality" and "similarity" between more immersive virtual environment and the actual place. Thereby, it was intended to conclude if 360º video combined to VR can be an advantage for the promotion of touristic destinations in Portugal.This research undertook a qualitative analysis, with data collection by questionnaire. It was concluded that, for the less immersive virtual environment, in which VR equipment was not used, "age" did not have a significant impact for participants' SP, contrary to "education level", that the higher is, the greater is the participants' SP. For the more immersive virtual environment, in which VR equipment was used, both variables proved to have significant influence on participants' SP. It was also found that both "age" and "education level" had influence on "similarity" and "expectancy/reality" concepts, concerning the comparison between VE and participants' visit to the first place. However, contrary to what was expected, for the comparison between VE and participants' visit to the second place, there was no interference of any of the variables. Finally, it was also possible to determine users' preference, regardless age and education level, for the use of VR equipment for 360º video visualization.